Islamic finance : issues in Sukuk and proposals for reform - Kamali, Mohammad Hashim; Abdul Karim Abdullah (Islamic Foundation, 2014)
A revolution is happening in Islamic finance including the rapid growth of the sukuk (Islamic bonds) market.